The last widow : [compact disc, unabridged] a novel - Slaughter, Karin, 1971- (Slaughter, Karin, 1971- Will Trent series., 2019)
Medical examiner Sara Linton and her partner Will Trent, an investigator with the Georgia Bureau of Investigation, rush into the heart of a deadly conspiracy that threatens to destroy thousands of innocent lives. When assailants abduct Sara, Will goes undercover to save her and prevent a massacre, putting his own life on the line for the woman and the country he loves.